Hyaluronic Acid–Zein Core-Shell Nanoparticles Improve the Anticancer Effect of Curcumin Alone or in Combination with Oxaliplatin against Colorectal Cancer via CD44-Mediated Cellular Uptake - Lu Liu; Shufang Yang; Feng Chen; Ka-Wing Cheng (Molecules, 2022)
Curcumin (CUR) has been reported to enhance the chemotherapeutic efficacy of oxaliplatin (OXA) in colorectal cancer (CRC) and inhibit OXA-induced side effects. However, shortcomings, including poor solubility and sensitivity to metabolic transformation, have greatly undermined its value in clinical applications. In this study, the potential of CUR-encapsulated hyaluronic acid (HA)–zein composite nanoparticles (HZ-CUR) as an oral adjuvant for OXA-based chemotherapy was assessed in representative CRC models in mice. Cell viability and colony formation assays in three human CRC cell lines showed that HZ-CUR had a stronger anti-CRC effect than free CUR when given alone and a stronger synergistic effect when combined with OXA, especially in HCT116 and HT29 cell lines. Western blotting, cellular uptake, and RNA interference assays revealed that OXA-induced upregulation of CD44 likely contributed to enhanced cellular uptake of HZ-CUR and thus the enhanced anticancer effect. The significantly improved anti-CRC effects and potential underlying mechanism of HZ-CUR alone and in combination with OXA were further validated in a subcutaneous xenograft and an in situ CRC model in mice. These findings support that HZ-CUR may be an effective oral adjuvant for OXA-based CRC chemotherapy that would not only improve its efficacy but also help reduce the associated side effects.